2008
DOI: 10.1016/j.exer.2008.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions involving congenital cataract T5P γC-crystallin mutant: A confocal fluorescence microscopy study

Abstract: The human lens crystallin gene CRYGC T5P is associated with Coppock-like cataract and has a phenotype of a dust-like opacity of the fetal lens nucleus and deep cortical region. Previous in vitro mutation studies indicate that the protein has changed conformation, solubility, and stability, which may make it susceptible to aggregation, as seen in cataractous lens and cell culture expression. To investigate the mechanisms leading to these events, we studied protein-protein interactions using confocal fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(39 reference statements)
0
11
1
Order By: Relevance
“…Among the three missense mutations (p.Thr5Pro, p.Arg48His, and p.Arg168Trp) in γC-crystallin, the effect of p.Thr5Pro on γC-crystallin has been well characterized in vitro by Liang's and several other groups. They showed that the mutation significantly impaired the secondary and tertiary structures, decreased the solubility and thermal stability of γC-crystallin [Fu and Liang, 2002] and affected its interaction with α-crystallin thereby [Fu and Liang, 2003;Liu et al, 2008]. Unlike the significant decrease in the regular secondary structure content by the p.Thr5Pro mutation [Fu and Liang, 2002], both structural modeling and spectroscopic analysis indicate that the p.Gly129Cys mutation did not affect the native secondary structure of γC-crystallin.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Among the three missense mutations (p.Thr5Pro, p.Arg48His, and p.Arg168Trp) in γC-crystallin, the effect of p.Thr5Pro on γC-crystallin has been well characterized in vitro by Liang's and several other groups. They showed that the mutation significantly impaired the secondary and tertiary structures, decreased the solubility and thermal stability of γC-crystallin [Fu and Liang, 2002] and affected its interaction with α-crystallin thereby [Fu and Liang, 2003;Liu et al, 2008]. Unlike the significant decrease in the regular secondary structure content by the p.Thr5Pro mutation [Fu and Liang, 2002], both structural modeling and spectroscopic analysis indicate that the p.Gly129Cys mutation did not affect the native secondary structure of γC-crystallin.…”
Section: Discussionmentioning
confidence: 87%
“…It is worth noting that α-crystallin in the lens acts as a molecular chaperone to protect misfolded proteins against aggregation [Horwitz, 1992]. Although α-crystallin could reduce the extent of aggregation, previous studies also show that the cataract-linked γ-crystallin mutants may affect α-crystallin function by aberrant protein-protein interactions [Banerjee et al, 2011;Liu et al, 2008]. It will be interesting to further investigate whether the p.Gly129Cys mutant also impairs or overloads α-crystallin function.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several reported cell lines expressing aggregation prone protein mutants and animal models with aggregation prone rhodopsin or c-crystallin mutants could be used to characterize a-crystallin as a therapeutic agent. [38][39][40] The fact that we have made a gC-aB that can easily be delivered to cells will allow for the characterization of a-crystallin in this setting. These models will also allow for characterization of any effect that the CPP has on in vivo use of a-crystallin.…”
Section: Discussionmentioning
confidence: 99%
“…The Thr5Pro substitution in human γC-crystallin affects stability and crystallin-crystallin interactions [6769]. Human γS-crystallin mutant Gly18Val lowers the transition midpoint of unfolding in GuHCl and reduces stability under conditions of heat denaturation [70].…”
Section: Etiology Of Cataractmentioning
confidence: 99%